Validity and Reliability of AH-EFT Module Among Breast Cancer Patients - Hasibuan, Sofyan Hadi; Said, Faridah Binti Mohd; Rashid, Norhashima Binti Abd.; Huda, Akhmad; Azizah, Fidrotin; Susanti, Dwi Agung (International Journal of Health Sciences, 2025)
Breast cancer, a heterogeneous disease, often metastasises, impacting prognosis. In Indonesia, adjuvant hormonal therapy (AHT) is the standard for hormone receptor-positive cancer, reducing recurrence and mortality. However, patients often face anxiety and depression during treatment. Emotional Freedom Techniques (EFT) are known to alleviate psychological stress. This study aims to evaluate the validity and reliability of the Adjuvant Hormonal Therapy with Emotional Freedom Technique (AH-EFT) module for breast cancer patients. A quantitative survey with a descriptive design assessed the content validity and reliability of the AH-EFT module. Six breast cancer care experts reviewed the module using a validity questionnaire and qualitative feedback. The result found that the content validity percentage reached 97%, with session suitability at 95%. The module’s reliability value was 0.934, indicating excellent consistency. The AH-EFT module is highly valid and reliable, making it suitable for guiding counselling and treatment for breast cancer patients in Indonesia and beyond.